Cylindrical Magnetorheological Fluid Variable Transmission Controlled by Shape-Memory Alloy - Song Chen; Kailin Jian; Xianghe Peng (Science and Technology of Nuclear Installations)
Centrifugal fan is an important component of a ventilation system in a nuclear power plant. In this paper, we proposed a magnetorheological speed-adjustment system controlled by shape-memory alloy for centrifugal fan. A theoretical analysis of the effect of the applied magnetic field on the viscoplastic flow between two cylinders in the speed-adjustment system is presented. The expressions for the velocity in viscoplastic flow and the torque transmitted by MR fluids are derived. A sliding mode SMA switch is proposed to modify the magnetic field acting on working gap under thermal effect. The results indicate that with the increases of applied magnetic field, the torque transmitted by MR fluid goes up rapidly.